Induced expression and functional role of heat shock protein 70 in Pentalonia nigronervosa (PnHsp 70) during banana bunchy top virus (BBTV) transmission - Indah Nuraini; Siti Subandiyah; Alan Soffan (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Heat shock protein 70 (Hsp70) plays a critical role in cellular stress responses and virus–vector interactions; however, its diversity and function in Pentalonia nigronervosa, the sole vector of banana bunchy top virus (BBTV), remain poorly understood. This study aimed to identify, characterize, and evaluate the expression of Hsp70/Hsc70 genes in P. nigronervosa during BBTV acquisition. RNA-seq datasets from viruliferous and non-viruliferous P. nigronervosa (SRX6918251–SRX6918252) were assembled and annotated, resulting in the identification of seven PnHsp70 and three PnHsc70 genes, which were deposited in GenBank (MW456681–MW456690). Molecular characterization included subcellular localization prediction, physicochemical analysis, structural modeling, and phylogenetic analysis. Differentially expressed gene (DEG) analysis was validated by quantitative real-time PCR (qRT-PCR) using plant access period (PAP) assays (0, 1, 5, 10, and 20 hours) on BBTV-infected banana plants. PnHsp70 showed high sequence similarity to Hsp70 proteins from aphids, particularly Myzus persicae and Acyrthosiphon pisum. Structural analyses revealed conserved Hsp70 domains and molecular features, whereas phylogenetic analysis grouped PnHsp70 with other hemipteran Hsp70 homologs. DEG analysis identified PnHsp1, PnHsp2, and PnHsc1 as BBTV-responsive genes. qRT-PCR demonstrated that PnHsp70 expression increased following BBTV acquisition, with peak induction at 1 hour and renewed upregulation at 20 hours PAP. These results suggest that BBTV acquisition induces PnHsp70 expression and support its potential involvement in BBTV–vector interactions. This study provides the first comprehensive characterization of Hsp70/Hsc70 genes in P. nigronervosa and offers new molecular insights into BBTV transmission.